A participatory, territory-rooted and change-oriented approach to assess the multi-criteria contribution of an agrifood value chain to sustainable development - Jonathan Vayssières; Alexandre Thévenot; Ivonne Acosta; Mathieu Vigne; Emmanuel Tillard (Indonesian Journal of Life Cycle Assessment and Sustainability, 2019)
Agrifood Value chains (AVCs) can be powerful driving forces for sustainable development. Multi-criteria analysis is particularly useful for supporting decision making on improvement measures in AVCs. Methodological guidelines are still needed to effectively integrate environmental and socio-economical assessment tools and indicators at this level.In this paper, we propose a participatory, territory-rooted and change-oriented framework. The framework is applied to analyse the contribution of the main local poultry AVC in Reunion Island to the sustainable development of the territory. The main stakeholders of the AVC participated in (i) identifying key territory challenges, (ii) selecting corresponding appropriate assessment methods and indicators, (iii) defining the perimeter of the AVC and (iv) the improvement scenarios to be explored, v) providing data inventory, and vi) interpreting the results of the assessment.Both the environmental life cycle assessment and the effect method fit the proposed framework particularly well. They were applied to the same AVC data inventory, improvement scenarios were explored and indicators were spatialized to distinguish the local impacts in the root territory and externalized impacts at the global scale.In the ecological dimension of our case study, most of the effects linked to the AVC activities which threaten resources conservation and ecosystem health are externalized. This is due to strong dependency on foreign resources: in the case of fossil energy and raw materials used for livestock feed, 82% of environmental impacts occur outside Reunion Island. In the socio-economic dimension, the employment created by the AVC is mainly local due to the use of local services, 89% of jobs are provided in Reunion Island. Improvement of on-farm eco-efficiency was shown to be a mitigation option that would significantly affect the impacts of the AVC. Human and ecosystem health, and resources conservation would be improved by respectively +2.2, +9.8 and +4.8,% at global scale. But the AVC industrial network and the community would also be negatively affected, by respectively -2.2 and -3.0%, at local scale. This study underlines trade-offs between the environmental and the socio-economic dimensions and methodological challenges associated with the effective integration of assessment methods originating from diverse disciplines.